(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
This article presents an in-depth analysis of modern innovative directions in dermatovenereology, with a focus on teledermatology, molecular genetic and epigenetic diagnostics, as well as novel therapeutic strategies. Based on data from international and domestic studies from 2020–2025, it is demonstrated that the integration of digital technologies, high-precision molecular methods, and targeted therapy is forming a new paradigm of personalized dermatological care. Clinical, organizational, and prognostic aspects of implementing these approaches are discussed.